Impact of traveling on transmission trends of human monkeypox disease: worldwide data based observational analysis - Meo, Sultan Ayoub; Al-Khlaiwi, Thamir; Al Jassir, Fawzi Fahad; Meo, Anusha Sultan (Frontiers in Public Health, 2023)
Background: Human monkeypox is an emerging viral zoonotic disease caused by a monkeypox virus (MPXV). This study aimed to investigate the impact of travelling on the transmission of human monkeypox disease and comprehend the link between monkeypox exported cases in the context of the global outbreak. Methods: We identified data from two leading health organizations, World Health Organization (WHO), and the Centers for Disease Control Prevention (CDC), as well as 40 documents that were identified through the search engines Web of Science, Pub-Med, Medline, EMBASE, Scopus, and Google Scholar using the keywords "monkeypox”, “human monkeypox”, “imported”’, “exportation” “travellers”, and “prevalence". Finally, two international organizations WHO, and CDC, and out of 40 documents, 10 (25.0%) were included in the analysis, and the remaining 30 (75.0%) documents were excluded. The studies originated from the United Kingdom, the United States of America, Singapore, Israel, the Republic of Korea, Taiwan, and India. The data on transmission trends and human monkeypox was recorded and analyzed. Results: The epidemiological data for exported monkeypox cases were analyzed jointly for understanding the transmission trends of exportations and the geographic context of the monkeypox outbreak. Ten people had a travel history, six had a travel history from Nigeria to the United Kingdom (2), Nigeria to the United States of America (2), Nigeria to Singapore (1) and Nigeria to Israel (1). Moreover, from Germany to Taiwan (1), Germany to the Republic of Korea (1) and the United Arab Emirates to India (2). Among these 10 people, all travellers were male (100%), with age ranges of 20-38 years, seven people (70%) developed clinical symptoms before the start of travel, three people (30%) developed symptoms 2-6 days after the travel, and one person (10%) developed clinical symptoms in the flight during the journey. Conclusions: The travelling can cause the spread of human monkeypox disease in various countries. The findings support the hypothesis that virus sources can travel and spread the disease from person to person and from region to region. The international health authorities must implement global preventive policies to control the burden of the disease both at regional and international levels.